Significado del cuidado cultural que realiza la madre rural en el recién nacido - García Flores, Nery Marisol (2016)
I go into the present of qualitative investigation of ethnographic trajectory, it came true at Puente Piedra group of houses of the city of Huamachuco, whose objectives they were to describe and to examine the care from the cultural context that the rural mother in the newborn baby accomplishes. Keys to which they accomplished the interview half-way structured and participating observation to to them notified eight informants. The referent theoretician was given in favor of the theory of Madeleine's trans-cultural care Leininger. Interviews to newborn babies' mothers allowing to identify and examining cultural commands that they generated like principal theme came true : “Helping it with love, they bring up jaquecitos ”, and sub-themes: preserving their beliefs, seeks to cure diseases your baby; I feel happy, if my child is not sick, but sad because we sometimes mistreat the things we use to care; that it allowed evidencing the significance of the cultural care in the newborn baby; expressing traditional practices broadcast generationally highlighting the assessment and practice of the same for the mother during care; and as we must preserve infirmary, negotiating and restructuring cares, that it allow coming to a culturally congruent care. Key words: Culture, newborn baby and cultural care.